Metallic Glasses and Their Oxidation - Wang, Xinyun; Zhang, Mao (Metal oxides series., 2023)
Metallic Glasses and Their Oxidation provides a comprehensive review of the structures, properties, preparations, processing and applications of metallic glasses. Special attention is paid to the oxidation behaviors and related mechanisms of metallic glasses that occur during their preparation, processing and application. The book's authors introduce basic knowledge of metallic glasses, including their structures, properties, processing techniques and applications. Then, the theories and techniques commonly used in oxidation investigation are highlighted, including thermal oxidation, native oxidation, stressed oxidation, powder oxidation and oxidation simulation. The book closes with the influence of oxidation on the structures and performances of metallic glasses, proposes measures to control oxidation, and discusses how to take advantage of oxidation to reinforce materials or create new materials.